Perceived Simultaneity and Temporal Order of Audiovisual Events Following Concussion - Wise, Adrienne; Barnett-Cowan, Michael (Frontiers in Human Neuroscience, 2018)
The central nervous system allows for a limited time span referred to as the temporal binding window (TBW) in order to rapidly determine whether multisensory events correspond with the same event. Failure to correctly identify whether multisensory events occur simultaneously and their sequential order can lead to inaccurate representations of the physical world, poor decision-making, and dangerous behavior. Damage to the neural systems that coordinate the relative timing of sensory events may explain some of the long-term consequences associated with concussion. The aim of this study was to investigate whether the perception of simultaneity and the discrimination of temporal order of audiovisual stimuli are impaired in those with a history of concussion. 50 participants (17 with concussion history) were recruited to complete audiovisual simultaneity judgment and temporal order judgment tasks. From these tasks, the TBW and point of subjective simultaneity (PSS) were extracted to assess whether the precision and or the accuracy of temporal perception changes with concussion, respectively. Results demonstrated that those with concussion history have a significantly wider TBW (less precise), with no significant change in the PSS (no change in accuracy), particularly for the TOJ task but not significant differences were found between the SJ and TOJ tasks. Importantly, a negative correlation between the time elapsed between the time of concussion diagnosis and the TBW width in the TOJ task suggests that precision in temporal perception does improve over time. These findings suggest that those with concussion history display either impairment in the perceived timing of sensory events or decision making and that monitoring performance in the SJ and TOJ tasks may be a useful additional assessment tool when making decisions about returning to regular work and play following concussion.